Enhancing Food Security through Improved Regional Transportation Infrastructure in ECOWAS - Lajuwomi, Oluwatosin Owolabi (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2024)
Food insecurity remains a significant challenge for developing nations, prompting initiatives like the Millennium Development Goals (MDG), Sustainable Development Goals (SDG), and Agenda 2030 to prioritise food security. In this context, regional transportation infrastructure is crucial for West Africa's economic development and growth. Notable advancements have reduced transportation times for goods, yet there is an urgent need to establish reliable transport infrastructure to ensure food security. This paper uses qualitative methods and secondary sources to investigate contemporary trends in regional transport infrastructure and its impact on food security in ECOWAS. It analyses challenges, opportunities, and potential strategies for improvement. The paper concludes that a multifaceted approach, including strengthened transportation infrastructure and effective monitoring and evaluation, is essential for addressing food security challenges in West Africa.